Morphological and molecular identification of root-knot nematodes infecting pomegranate in Assiut Governorate, Egypt - El-Qurashi, M. A.; El-Zawahry, Aida M. I.; Abd-El-Moneem, K. M. H.; Hassan, Mohamed I. (Journal of Phytopathology and Disease Management, 2017)
Root-knot nematodes are the most plant parasitic nematodes causing serious damage in pomegranate. Accurate identification of Meloidogyne species is ofÂ great importance for effectiveÂ management of root-knot nematodes. Morphological identification of Meloidogyne spp. has been long and extensively used. However, molecular diagnostics was reported as a replacement or a complement method. Examination of the perineal patterns of the female was typically identified the nematode isolates as M. javanica which was dominant in all five pomegranate samples. For further confirmation of identification, a polymerase chain reactionÂ (PCR)-basedÂ assay with two species-specific sequence characterized amplified regions (SCAR) primer sets was performed. The Fjav/Rjav and MJ-F/MJ-R primers efficiently amplifiedÂ SCAR markersÂ of 670 and 517 bp, respectively, which were previously reported for M. javanica. These results support that SCAR markersÂ are a powerfulÂ toolÂ for rapid and effective detection and could be used as a complementary tool together with the morphological identification of root-knot nematodes.